(untitled) (Journal of Dissability Studies and Research (JDSR), 2023)
In Indonesia, Among 20,87 million children in 2005, only those who received a good education such as Playgroups, Playgrounds and others managed by the government or private sector amounted to around 60%, this number illustrates the number of children touched by education, even though the next generation of a nation is children. The quality of the child depends on the quality of his growth and development, one of which is influenced by the provision of stimulus education. If a child loses the opportunity to learn at an early age, then his brain development will also be hampered and will be below average. An important period in the growth and development of children is toddlerhood, because this period is a period of basic growth that will influence and determine the next child’s development, so that any abnormalities or even the slightest deviation will reduce the quality of the nation’s next generation in the future. The process of growth and development of children runs naturally which is characterized by patterns and characteristics that can be determined beforehand. The purpose of this study was to determine the effect of educational stimulation on the intelligence development of children aged 3-6 years. This study used a pre-experimental method with a one-group pretest-posttest design. The sample in this study were 20 students of Kindergarten Baiturrahim Jambi who were selected based on randomization. Before being given treatment, the researcher carried out an initial IQ test using the WPPSI (The Wechsler Preschool and Primary Scale of Intelligence) and then was given treatment in the form of educational stimulation. After completing the treatment, the final IQ test was carried out again, to see the development of intelligence in children. The data obtained were analyzed by means of a two-sample t-test in pairs. The results of this study showed an increase in IQ scores at the time of the pre-test and post-test for verbal IQ of 6.0 units (92.1 vs 98.1); p value <0.001, achievement IQ of 6.6 units (104.4 vs 111.0); p value <0.001, full IQ of 7.7% or 7.5 units (97.5 vs 105.0); p-value <0.001; in girls IQ of 100.8 vs 107.5 units; p-value 0.002; and boys’ IQ of 94.2 vs 102.5 units; p-value < 0.001. From this study it can be concluded that educational stimulation has a significant effect on increasing the development of verbal intelligence, achievement and full IQ, and it is seen that girls aged 3-6 years have a higher level of intelligence than boys.